Reconciling Knowledge: A Comparative Analysis of Amin Abdullah’s Integration-Interconnection Paradigm and Syed Naquib Al-Attas’s Islamization of Science - Purwaningtyas, Dhita Ayomi; Delahara, Nindhya Ayomi (Jurnal Kawakib, 2024)
This study explores Prof. Dr. Amin Abdullah's Integration-Interconnection paradigm, which seeks to reconcile religious and secular sciences in Islamic educational contexts, particularly within Indonesian universities. While Abdullah's model emphasizes the harmonious integration of diverse scientific domains through a metaphorical "Spider Web of Knowledge," this paper critiques the paradigm using Syed Muhammad Naquib al-Attas's Islamization of Science perspective. Al-Attas argues for a selective integration that eliminates secular influences incompatible with Islamic principles, a view that contrasts with Abdullah's more inclusive approach. This research critically analyzes these two frameworks to assess their efficacy in addressing Islamic academia's contemporary challenges. Findings suggest that critical filtering of secular knowledge may enhance the Islamic identity in scientific scholarship.